Astrocytic CXCL5 hinders microglial phagocytosis of myelin debris and aggravates white matter injury in chronic cerebral ischemia - Qian Cao; Jian Chen; Zhi Zhang; Shu Shu; Yi Qian; Lixuan Yang; Lushan Xu; Yuxin Zhang; Xinyu Bao; Shengnan Xia; Haiyan Yang; Yun Xu; et al. (Journal of Neuroinflammation, 2023)
Abstract Background Chronic cerebral ischemia induces white matter injury (WMI) contributing to cognitive decline. Both astrocytes and microglia play vital roles in the demyelination and remyelination processes, but the underlying mechanism remains unclear. This study aimed to explore the influence of the chemokine CXCL5 on WMI and cognitive decline in chronic cerebral ischemia and the underlying mechanism. Methods Bilateral carotid artery stenosis (BCAS) model was constructed to mimic chronic cerebral ischemia in 7–10 weeks old male mice. Astrocytic Cxcl5 conditional knockout (cKO) mice were constructed and mice with Cxcl5 overexpressing in astrocytes were generated by stereotactic injection of adeno-associated virus (AAV). WMI was evaluated by magnetic resonance imaging (MRI), electron microscopy, histological staining and western blotting. Cognitive function was examined by a series of neurobehavioral tests. The proliferation and differentiation of oligodendrocyte progenitor cells (OPCs), phagocytosis of microglia were analyzed via immunofluorescence staining, western blotting or flow cytometry. Results CXCL5 was significantly elevated in the corpus callosum (CC) and serum in BCAS model, mainly expressed in astrocytes, and Cxcl5 cKO mice displayed improved WMI and cognitive performance. Recombinant CXCL5 (rCXCL5) had no direct effect on the proliferation and differentiation of OPCs in vitro. Astrocytic specific Cxcl5 overexpression aggravated WMI and cognitive decline induced by chronic cerebral ischemia, while microglia depletion counteracted this effect. Recombinant CXCL5 remarkably hindered microglial phagocytosis of myelin debris, which was rescued by inhibition of CXCL5 receptor C-X-C motif chemokine receptor 2 (CXCR2). Conclusion Our study revealed that astrocyte-derived CXCL5 aggravated WMI and cognitive decline by inhibiting microglial phagocytosis of myelin debris, suggesting a novel astrocyte-microglia circuit mediated by CXCL5-CXCR2 signaling in chronic cerebral ischemia.